A weak-form meshfree coupled with infinite element method for predicting acoustic radiation - Wu, Shaowei; Xiang, Yang (Engineering analysis with boundary elements, 2019)
To improve the computational accuracy and eliminate the element matching in the traditional method based on the finite and infinite elements, the coupling of the meshfree weak-form method with the variable order infinite acoustic wave envelope element (WEE) is studied in this paper and achieved by forming continuous acoustic shape function on an artificial interface, by which the infinite domain is divided into two subdomains where the meshfree and WEE methods are applied respectively. A coupled meshfree weak-form method is developed for use in predicting acoustic radiation in infinite domain. A key feature of the present method is the ability of properly modelling the amplitude decay of the outgoing travelling wave and significantly improving the prediction accuracy. The impacts of the meshfree shape function approximation/interpolation scheme and the space scale of the region used for the coupling on the proposed method are investigated. Simulation and experiment are performed to test the applicability and performance of the method, and show that the method is a valuable approach for predicting exterior acoustic radiation in infinite domain.